1979
DOI: 10.1111/j.1467-9450.1979.tb00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin conductance as a function of alcohol during motor approach towards a noxious goal

Abstract: During hand movement towards a goal involving electric shock, increased SCR amplitudes were observed for increased threat. In the presence as well as in the absence of alcohol, shock probabilities of 0.50 and 1.00 induced stronger SCRs than no‐shock control conditions. The outcome was related to behavioural measures of hesitation where an alcohol dose of 0.9 g/kg reduced hesitation significantly. It was concluded that the cognitive appraisal of threat remained unaffected by alcohol, whereas fear as reflected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The consumption of alcohol, but not of a placebo, markedly attenuated the magnitude of physiological responses to the stressors. A consistent finding across several studies was a reduction in the magnitude of heart rate and skin conductance responses to stress (e.g., Finn, Zeitouni, & Pihl, 1990;Lindman, Alexanderson, & Kvarnstrom, 1979;Sher & Levenson, 1982Stewart, Finn, & Pihl, 1992;Stewart & Pihl, 1994;Wilson, Abrams, & Lipscomb, 1980). Some studies have not shown SRD effects of alcohol on measures of autonomic reactivity to stress (e.g., D. B.…”
Section: Physiological Effects Of Alcohol In Ptsdmentioning
confidence: 77%
“…The consumption of alcohol, but not of a placebo, markedly attenuated the magnitude of physiological responses to the stressors. A consistent finding across several studies was a reduction in the magnitude of heart rate and skin conductance responses to stress (e.g., Finn, Zeitouni, & Pihl, 1990;Lindman, Alexanderson, & Kvarnstrom, 1979;Sher & Levenson, 1982Stewart, Finn, & Pihl, 1992;Stewart & Pihl, 1994;Wilson, Abrams, & Lipscomb, 1980). Some studies have not shown SRD effects of alcohol on measures of autonomic reactivity to stress (e.g., D. B.…”
Section: Physiological Effects Of Alcohol In Ptsdmentioning
confidence: 77%